2012
DOI: 10.1016/j.jaac.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health in Low-to-Moderate Risk Preterm, Low Birth Weight, and Small for Gestational Age Children at 4 to 5 Years: The Role of Early Maternal Parenting

Abstract: Children with LTM perinatal risk were at a small increased risk for emotional difficulties but did not differ significantly from other children of similar social backgrounds in their risk for generalized mental health problems. These findings support a biological and socio-economic, rather than parenting, pathway to psychological risk in children born with LTM perinatal risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…These results are consistent with prior research that found higher rates of total difficulties and anxiety symptoms 8 and findings from studies of older children born very preterm that have found higher rates of total psychiatric disorders and anxiety disorders. 1 Among older school-age and adolescent children born either very preterm or very low birth weight, the odds of anxiety disorders have ranged from 3 to 6 times that in control children, 1,2,36 with SAD and GAD being particularly prominent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with prior research that found higher rates of total difficulties and anxiety symptoms 8 and findings from studies of older children born very preterm that have found higher rates of total psychiatric disorders and anxiety disorders. 1 Among older school-age and adolescent children born either very preterm or very low birth weight, the odds of anxiety disorders have ranged from 3 to 6 times that in control children, 1,2,36 with SAD and GAD being particularly prominent.…”
Section: Discussionsupporting
confidence: 91%
“…6 Recent evidence supports an increased rate of psychiatric symptoms in late preterm children as well, particularly ADHD, 7 “emotional”, and anxiety symptoms. 8 Other investigations, however, have failed to detect a difference in the rates of psychiatric symptoms between late preterm and full term children. 9 The small body of research evaluating the psychiatric outcomes of late preterm children has been limited by the reliance on symptom checklists, retrospective review of records or by investigation of child outcomes at a broad range of developmental stages.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, studies have shown that parents of a child born with perinatal risk may be more "protective" or attentive of their child given the high-stress context of birth complications. 33 We urge caution in the interpretation of this finding, given that the stability and mechanism of this effect are not clear from our results.…”
Section: Discussionmentioning
confidence: 63%
“…(19) Although there is less evidence in the LP population, available evidence supports an increased rate of psychiatric symptoms in LP children as well, including “emotional”, and anxiety symptoms. (20,21) We have also previously noted increased rates of psychiatric disorders, including a four-fold risk for anxiety disorders, at preschool age among LP children in the cohort to be examined in the analyses presented here. (22) Elevated rates of generalized anxiety disorder and separation anxiety disorders were found in this group.…”
mentioning
confidence: 63%